The effect of adding physician recommendation in digitally-enabled outreach for COVID-19 vaccination in socially/economically disadvantaged populations - Kamal Sumar; Lisa Blue; Gina Fatahi; Mehek Sumar; Stephanie Alvarez; Pedro Cons; Nathalie Valencia; Zachary Williams; Atiq Bhatti; Sairam Parthasarathy; Chyke A. Doubeni (BMC, 2024)
Abstract Introduction People from backgrounds that are economically/socially disadvantaged experienced disproportionately high COVID-19 death rates and had lower vaccination rates. Effective outreach strategies for increasing vaccine uptake during the pandemic are not fully known. Among patients receiving care at a Federally Qualified Health Center, we tested whether community engaged digitally-enabled outreach from a trusted clinician messenger increased COVID vaccine uptake. Study design, setting, and participants A 3-parallel-arm randomized controlled trial with a hybrid effectiveness-implementation design was conducted among patients ≥ 18 years old on study enrollment during 2021 with 1,650 assigned in 3:10:20 ratio; 2,328 were later selected for two subsequent implementation rounds. Interventions From April 13 to June 10, 2021, patients were proactively sent a text-messaging invitation to make an appointment for vaccination as part of the routine practice with a link to frequently asked questions (Arm 1, n = 150) with added personalized clinician recommendation alone (Arm 2, n = 500) or with enabled 2-way SMS messaging feature (Arm 3, n = 1,000). Further implementation used messaging addressing vaccine hesitancy (n = 1,323) or adverse reactions to vaccines (n = 1,005). Main outcomes and measures The primary outcome was the completion of the first SARS-Cov-2 vaccine dose determined at 14, 30 and 90 days after outreach. Results Of 1,650 patients in effectiveness Arms, 61% was female. Vaccination rates for Arms 1, 2, and 3, were 6% (n = 9), 5.4% (n = 27) and 3.3% (n = 33) at 14 days, and 11.5% (n = 17), 11.6% (n = 58), and 8.5% (n = 85) at 90 days, respectively, which were similar in pairwise comparisons. At 90 days, vaccination rates were similar across the two implementation rounds (3.9% vs. 3.6%) and were similar to the rate (3.3%) among patients who were not selected for intervention arms or implementation rounds (n = 8,671). Conclusions Digitally-enabled outreach that included SMS messaging outreach augmented with clinician recommendations did not improve COVID-19 vaccination rates. Trial registration This study is registered at ClinicalTrails.gov Identifier: NC-T04952376.